Effort to differentiate essential tremor plus and dystonic tremor using whole exome sequencing: an exploratory study - Sanjay Pandey; Sanjay Pandey; Navneesh Yadav; Shreya Dinesh; Shreya Dinesh; Chandra Shekhar Rawat; Chandra Shekhar Rawat; B. K. Thelma (Dystonia)
BackgroundThe clinical differentiation between essential tremor plus (ETP) and dystonic tremor (DT) is challenging. This study aimed at the genetic diagnosis of ETP and DT.MethodsWhole exome sequencing was performed on 50 probands (ETP = 25; DT = 25) and analysed to identify variants in known genes linked with dystonia and essential tremor plus phenotypes.ResultsWe identified pathogenic/likely pathogenic variants [THAP1 (n = 1) and ANO3 (n = 1)] in two patients with DT. In addition, one DT patient had a variant of uncertain significance in FUS and four patients had benign variants [CIZ1 (n = 1), COL6A3 (n = 1), GCH1 (n = 1), TENM4 (n = 1)]. One patient with ETP was detected to have a variant of uncertain significance in TENM4 and five patients with ETP had benign variants [COL6A3 (n = 2), VPS16 (n = 1), TAF1 (n = 1), KMT2B (n = 1)].ConclusionGenetic studies may be in an important biomarker in differentiating patients with ET plus from DT which is challenging in a clinical setting.